A formação continuada na construção da identidade docente: o curso Educação Africanidades Brasil - Barbosa, Maria José Candido (2009)
In this work we propose to investigate the implications of cultural landscapes in the post-modern models of Continuing Education of the teachers and their relation to the (re)construction of teachers identity. We use the contributions of Cultural Studies, which centrality given to culture as lead us to put the category identity as the main point of our research for identity, considering it as a cultural construction that is established in modern societies at the end of the twentieth century and going on in the century 21. To do this, we use the principles of French discourse analysis as a qualitative research approach, by examining the discursive practices of 04 teachers of the educational system of João Pessoa, who participated of the course Educação- Africanidades-Brasil; and analyzing the documentary corpus composed of legislation, Continuing Education parameters and policies of affirmative action in Brazil through decrees, ordinances, declarations, recommendations and other prescriptive legislation and educational policies. The research results lead us to recognize the Continuing Education as a discursive event that allows the (re)construct of teachers identities to face the fragmentation of the post-modern cultural landscapes.